Liberdade e escolha em Jean-Paul Sartre - Gonçalves, Nádia Mariana Gomes (2013)
This work intends to conduct a handling the concepts of Freedom, Choice and Others, from the perspective of the French existentialist philosopher Jean-Paul Sartre as having reference works Being and Nothingness, Existentialism is a Humanism and No Exit.The principle will be exposed to the theme of freedom is inseparably linked to the condition of man\'s choice to do so, leave the deep thinking that Sartrean man first exists, lives according to their freedom responsibly and choose what you want to be, not because there is no metaphysical being who can determine its path, so that later the man can attain its essence. However, during the search for the essence encounters freeman Other freemen taking ai to a series of conflicts. This question about the existence of other free subject is better explored in the second chapter, which is also seen in phenomenology, the existence and the problem of the existence of other free conscience, moreover, will be presented in the second chapter the question of looking relations and limited freedom for Others. And finally, the last chapter will be a detailed analysis of the play No Exit, about the prospect of the two previous chapters.